perencanaan struktur gedung 9 lantai hotel sky sea view jepara - Adi, Ristyanto (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2021)
As part of supporting the tourism sector, the hotel will add to the regional economic value. Based on Indonesian National Standard regulations including: PPIUG 1983, SNI 03-1726 2019, SNI-03-2847, PPPURG, SKSNI-T-15-1991-03 1991. The material uses 30 MPa concrete, the quality of reinforcing steel is 400 MPa. 12 cm thick floor slab with reinforcement X D10-200 and Y D10-200. Roof plate 10 cm thick reinforcement X D10-250 and Y D10-250. Main beam 60x30 cm bearing reinforcement 4D20 field reinforcement 4D20 support stirrup D10-200 field stirrup D10-250 and reinforcement for 4D12. Beam 45x25 cm bearing reinforcement 5D20 field reinforcement 5D20 support stirrup D10-150 field hoop D10-150 and reinforcement for 2D12. Child beam 35x20 cm bearing reinforcement 4D20 field reinforcement 4D20 support stirrup D10-100 field hoop D10-150 and reinforcement for 2D12. Sloof beams 60x30 cm bearing reinforcement 4D20 field reinforcement 4D20 stirrups D10-250 and reinforcement for 4D12. Column 50x50 with 8D20 reinforcement, stirrups D10-200.